2021
DOI: 10.12659/msm.930168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infection with SARS-CoV-2 on the Male and Female Reproductive Systems: A Review

Abstract: Coronavirus Disease-2019 (COVID-19) is a rapidly spreading pandemic that began at the end of 2019. COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Reproductive health has always been one of the most important healthcare problems, and the impacts of COVID-19 on the reproductive systems have become an emerging topic. The effects of infection with SARS-CoV-2 on males are more harmful than on females. The outcomes of pregnancy also can show the condition of male and female repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 89 publications
0
15
0
1
Order By: Relevance
“…Published reports are limited by small study groups, lack of the control group, and the absence of follow‐up examinations during recovery warranting further research and in‐depth exploration of the topic. 9 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published reports are limited by small study groups, lack of the control group, and the absence of follow‐up examinations during recovery warranting further research and in‐depth exploration of the topic. 9 …”
Section: Introductionmentioning
confidence: 99%
“…There is ultimately too little information to draw reliable conclusions regarding the effects of the virus on male reproduction. Published reports are limited by small study groups, lack of the control group, and the absence of follow‐up examinations during recovery warranting further research and in‐depth exploration of the topic 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outlier ratio of ALT/AST and gamma-glutamyl transferase continues to decline and was less than 10%. 25 Multivariant metabotyping study by Holmes et al 39 41 A meta-analysis on more than 3 million reported global cases conformed that male COVID-19 infected patients had 3 times the odds of requiring the intensive treatment unit admission and higher odds of death compared to women. 42 In a recent in vitro study, it was shown that 17β-estradiol can reduce SARS-CoV-2 infection, the group also showed that TMPRSS2 gene expression can be reduced by estrogen after SARS-Cov-2 infection, TMPRSS2 is involved in COVID-19 infectiveness capacity.…”
Section: Covid-19 Recovery: Long-term Side Effects and Lingering Symp...mentioning
confidence: 99%
“…COVID‐19 was not just age bias but also sex bias towards severe disease. 41 A meta‐analysis on more than 3 million reported global cases conformed that male COVID‐19 infected patients had 3 times the odds of requiring the intensive treatment unit admission and higher odds of death compared to women. 42 …”
Section: Introductionmentioning
confidence: 99%